A Comparison of Judicial Review in Indonesian Constitutional Court and French Constitutional Council - Samsudin, Muhammad Iqbal (Indonesian Comparative Law Review, 2022)
One of the advances in contemporary legal and governmental ideas to arise in the 20th century was the notion of establishing a Constitutional Court. A constitutional court is a high court that focuses on constitutional law issues. Its primary authority is to rule on whether laws that are reviewed are in fact in line with constitution or not. The purpose of this study is to compare the judicial review functions and institutional aspect of the Indonesian Constitutional Court with the French Constitutional Council. It explains the distinctions and similarities between the roles of the Indonesian Constitutional Court and the French Constitutional Council as judicial entities allowed to conduct judicial reviews of statutes in accordance with the constitution. The research method employed is library research, while the research approach is a statutory approach and a comparative approach. The study shows that the Constitutional Courts in France and Indonesia have certain similarities and differences that come from the issue of court’s authority, nature of decision, complainant party, and qualification and composition of justices.